Identifikasi Identifikasi Produk Cacat Briket Tempurung Kelapa Menggunakan Six Sigma dan Fuzzy Analytical Hierarchy Process (FAHP) - Shintya Kurniawan; Elly Wuryaningtyas; Emmy Nurhayati (Universitas Sarjanawiyata Tamansiswa, 2022)
CV. Bintang Yasa Abadi is a management company coconut shell waste into briquette products and is marketed for export to the Middle East. Poor quality control process results in a large number of inappropriate products and becomes a problem during production process. Purpose of this study to determine the level of company productivity, the factors that cause non comformances and improvement. The method used in this study is the six sigma method and improvements effort the assesment priority using the FAHP method so that the resulting assesment is accurate and objective.The results of the research using the six sigma method resulted in a DPMO 7.604,74, a sigma value of 3,92, and the factors causing defect came from machine, material, environment, method, human, and measurement. The results og the FAHP assessment resulted in the highest weight in the effort to improve the evaluation measurement of quality of water content and density of briquattes 0,364, supervision of workers in the cutting section according to the SOP with repair weight of 0,202 and checking the dry content of coconut shells using a Moisture Meter (measuring water humidity) with repair weight of 0,718 improvement.